DIAGNOSIS OF OVERWEIGHT AND OBESITY IN TEENAGERS FROM A PUBLIC SCHOOL OF FORTALEZA-CE (Fiep Bulletin - online, 2014)
The overweight and the obesity are increasing, not only in the developed countries. Recently the World Health Organization (WHO) considered the obesity the newest world syndrome. In Brazil, studies about obesity and overweight prevalence are even scarcer, but specialists and researches have a sure: the overweight and obesity developing is reaching ages each time younger. Therefore, this study aims to verify the obesity and overweight index in teenagers from both sex in a public school from Fortaleza - CE. The study had a transversal character and was done in the Colégio Liceu do Ceará, with students from 14 to 19 years old. Was done a training to the evaluators to guarantee the precision of the measures and faithfulness in the study. To the data collect, was used a flexible ruler (Easy read) with a precision of 1 cm and a digital balance (Plenna) with a capacity to 150 kg. Was measured the weight and the stature to determinate the Body Mass Index (BMI), according to the criterions of CDCK. The results were analyzed according to a descriptive statistic and to the "Qui-quadrado" tests and Person test. From the 284 students measured, 154 are females (54,5%) and 130 (45,5%). The overweight and the obesity were higher to the sex male, prevailing in the age of 14 and 16 years old. The "Qui-quadrado" test verified dependence between sex and nutritional classification. The BMI and the WC (waist circumference), showed an association of r=0,64 and the realization of physical activity was the same for both sex. The obtained results in this study suggest a nutritional support to improve the health condition of these students, beyond the incentive to physical activity practice at home or even in their schools.
Keywords: obesity; overweight; students